Seroprevalence in Argentinian healthcare workers after vaccination with Sputnik V - Santonato, Daniela; Malvicini, María A.; Novau, Andrea; Torres, Silvio F.; Siaba Serrate, Alejandro; Romano, María V.; Brenzoni, Pablo G.; Fabbro, Leonardo; Paulosky, Laura; Cornistein, Wanda (International Journal of Infection Control, 2022)
Background: Healthcare workers (HCW) were deeply affected by coronavirus disease 2019 (COVID-19). Therefore, vaccination of this population is crucial. However, data on Sputnik V vaccine are sparse. Objective: The aim of this study was to evaluate serological responses in HCWs following two doses of Sputnik V vaccine. Methods: A cross-sectional study was conducted at a tertiary-care private teaching hospital between April and May 2021. HCWs without a history of COVID-19 3 or more weeks after the second dose of Sputnik V had a fresh serum sample extracted and processed using Abbott® SARS-CoV-2 IgG II Quant. Values equal to or over 50 arbitrary units (AU)/mL were considered positive. Primary outcome was the proportion of participants who developed antibodies 21 or more days after the second dose of Sputnik V. Secondary outcomes were concentration of anti-spike IgG antibodies and comparison of such concentrations between samples taken 3–5 weeks and more than 5 weeks after the second dose. Results: The entire population developed anti-spike IgG antibodies. The median antibody concentration was 1234.8 AU/mL. When analysing days to extraction from second vaccine dose, there was no statistical difference between 21 and 35 days versus more than 35 days. Conclusion: Vaccination with Sputnik V in HCW at our institution demonstrated an efficacy of 100% in achieving quantifiable anti-spike IgG antibodies 21 or more days after the second dose.